Exploring Clinical Supervision Model Employed by Qualified Nursing Staff at Mbarara Regional Referral Hospital and Its Contribution to Students’ Competencies. - Opio, Mark (Student’s Journal of Health Research Africa, 2021)
Background. Clinical supervision is an instructional face-to-face interaction between the supervisor and the supervisee which enables the supervisee to perform his/her job better (ABIDDIN, 1980). There is a various model which is being used to in supervision of students which includes coaching, mentorship, preceptorships, and individualized model when used leads to the acquisition of knowledge, skills, improves performance and students competencies. The purpose of the study was to explore clinical supervision models employed by qualified nursing staff at MRRH and their contribution to students’ competencies Methodology. A qualitative descriptive design was employed in this study. The purposive sampling method was used to recruit 9 participants. Data collection was done by in-depth interview method using a semi-structured interview guide. Inductive content analysis was used to generate the themes and categories. Results. The study findings revealed three themes that emerged as the participants’ descriptions of the clinical supervision model. These themes included coaching, self-directed learning, and individualized learning. Conclusion. The supervisory model used by the qualified staff in this study was coaching; mentoring, self-directed learning that enhances professional growth and skills competencies as well as promoting relationships between the supervisor and the supervisee. Recommendation. The use of supervisory models in clinical practice should be emphasized so that nurse practitioners use them to provide the best learning approach that enables students to gain competencies. Integration of supervisory models in the nurse curriculum so that they know the importance of when they qualify and utilize them during the supervision of students to maximized learning in a clinical setting.